STUDYING THE DEGREE OF SOIL SALINIZATION IN EXPERIMENTAL AREAS - Ismailova Khalavat Djabarovna (Web of Journals Publishing, 2024)
To conduct experiments in experimental plots, the degree of salinization of soil fields was studied by the initial amount of salts in them. The results obtained showed that the soils of the first experimental field have a heavy mechanical composition and, due to the presence of mineralized Syzob waters in the surface of the earth, are somewhat more saline than the soils of the second field. According to the results of our long-term studies of cotton in the Karshi steppe, watering the crop ahead of schedule or delaying watering, as well as an excessive decrease or increase in irrigation rates, lead to a decrease in yield and soil salinization.
Keywords: watering, irrigation regime, soil salinization, mineralization, mechanical composition, ground water, dry residue, depth, yield.